Progression of Coronavirus cases in Latin America: Comparative analysis one week after the start of the pandemic in each country - Araujo-Banchon, William J.; Aveiro-Róbalo, Telmo Raúl; Fernandez, Maria F.; Castro-Pacoricona, Diana; Moncada-Mapelli, Enrique; Chanava, Walter; Mejia, Christian R. (Kasmera, 2020)
The pandemic generated by COVID-19 progresses differently when it reaches each territory, the progression of Coronavirus cases in the first week of the pandemic was compared in each country in Latin America. A descriptive study was carried out, with the information of the confirmed cases in each country, this since the first case was announced in each territory. Progressions are shown in graphical forms, with total cases and adjusted for population density. Uruguay and Panama were the countries that stood out from all those evaluated, they had a greater number of confirmed cases weighted in the first week of the pandemic. Likewise, these two countries were also those with the highest number of absolute cases (not weighted by the number of population), as well as the country of Venezuela; that he is even thought to have more cases, due to his political problems. There were some differences in the number of cases that occurred in each Latin American country at the end of its first week of the COVID-19 epidemic; this could be due to the government policies that were taken before and during those first days, which should serve as an example for acting in future similar cases.